THE ISLAMIC PERSPECTIVE ON SYMBOLIC INTERACTION THEORY - Daulay, Mahmud Yunus; Rubino, Rubino; Mailin, Mailin (Reflektika, 2025)
The discussion of symbolic interaction emphasizes more on the motives underlying human actions. Symbolic interaction states that all human actions are based on two motives, namely the motive for (in order to motive) and the motive because (because to motive). Both motives are in the mind of a person who does the act and no one else knows. In Islam, this motive can be called the intention that underlies the act. This intention is important because it is the cause of the acceptance or rejection of an action. Therefore, it is necessary to critique this theory from the perspective of Islamic communication. The results of the criticism of this theory from an Islamic perspective are, first, behavior must be carried out with good motives and intended because of God as the owner of power. Although sometimes in life, there are also many motivations for human behavior that are for other than God. Second, human behavior is not entirely born of his will, but there is also God's will in it. Third, Islam recommends that confirmation be carried out to see the motives of actions.